Importance of angle correction in transcranial color-coded duplex insonation of arteries at the base of the brain - Lepić, Toplica; Veljančić, Dragana; Jovanikić, Olivera; Lepić, Milan; Slankamenac, Petar; Raičević, Ranko (Vojnosanitetski pregled, 2016)
Background/Aim. Transcranial color-coded duplex (TCCD) sonography allows visualization of the vessels being examined and measurement of the angle of insonation. The published literature suggests that blood vessels are insonated at the angle lower than 30 degrees, hence no correction for the angle is necessary. The aim of this study was to determine the availability of intracranial blood vessels for insonation, and the percentage of arteries and their segments which can be insonated at the angles lower than 30 degrees. Methods. The study included 120 patients (mean age 51). For each of the segments the angle of insonation was registered based on TCCD vizualization, and hemodynamic parameters were measured. The angle of insonation was measured using combined B-mode and color Doppler vizualization, as the angle between the direction of the ultrasound beam and the axis of the shown arterial segment. Results. The total success rate of insonation was 86.33% (1,554 out of 1,800). The mean angle of insonation value in all the examined arterial segments was 42 degrees. The insonation angle was higher than 30 degrees in about three quarters of the examined segments, especially in the A2 segment of the anterior cerebral artery (98%), the P1 segmet of the posterior cerebral artery (87%) and in the terminal internal carotid artery (83%). The A1 segment of the anterior cerebral artery showed the best insonation conditions with the angle of insonation lower than 30 degrees in 53% of the cases. Conclusion. The presented results of angles of insonation measurements for the anterior, middle and posterior cerebral arteries and their segments, as well as the terminal portion of the internal carotid artery clearly indicate that their average values in tested segments were very often higher than 30 degrees, which can cause an error in blood flow velocity measurement that cannot be ignored. The results confirm the necessity of correcting flow velocity values on the basis of the angle of insonation in TCCD sonography.  Key words:            ultrasonography, doppler, transcranial; ultrasonography, doppler, duplex; blood flow velocity; carotid artery, internal; anterior cerebral artery; middle cerebral artery